Identification of AC025811.3 and AC012354.6 as two critical survival-related lncRNAs for uterine corpus cancer - Lu Pu; Rui Ou; Zhaomin Deng; Hao Jiang (PLoS ONE, 2026)
Uterine corpus endometrial carcinoma (UCEC) ranks as the most frequently diagnosed gynecologic malignancy and the second leading cause of gynecologic cancer-related mortality. Long non-coding RNAs (lncRNAs) have emerged as critical regulators of gene expression and tumor biology; however, their prognostic significance in UCEC remains largely unexplored. To systematically identify survival-associated lncRNA biomarkers, we integrated clinical and transcriptomic data from two independent cohorts: TCGA-UCEC (548 tumor, 35 normal) and CPTAC-Uterus (102 tumor, 15 normal). Following upper quartile normalization and ComBat-based batch effect correction, differentially expressed lncRNAs (FDR < 0.01, |log2FC| > 2) were identified using Student’s t-test. The intersecting set of consistently dysregulated lncRNAs from both cohorts was subjected to Cox proportional hazards regression to identify survival-associated candidates. Functional inference was performed through Spearman correlation with protein-coding genes and Gene Set Enrichment Analysis (GSEA) of KEGG pathways. A total of 550 lncRNAs were consistently downregulated and 148 were upregulated in UCEC across both cohorts. Cox regression identified 30 survival-associated lncRNAs (FDR < 0.01), all with elevated expression correlating with worse overall survival. The top two candidates, AC025811.3 and AC012354.6, showed significant stage-dependent expression patterns across FIGO stages I–IV and were functionally enriched in immune regulation and carbohydrate metabolism pathways. In conclusions, AC025811.3 and AC012354.6 represent novel candidate prognostic lncRNA biomarkers in UCEC. Experimental validation, including FISH-based tissue localization and staged quantification, and functional assays, is warranted to confirm their biological roles.